Hemostatic mechanism underlying microbubble-enhanced non-focused ultrasound in the treatment of a rabbit liver trauma model. Issue 2 (January 2017) - Zhao, Da-wei; Tian, Meng; Yang, Jian-zheng; Du, Peng; Bi, Jie; Zhu, Xinjian; Li, Tao
The aim of our study was to investigate the hemostatic mechanism underlying microbubble-enhanced non-focused ultrasound treatment of liver trauma. Thirty rabbits with liver trauma were randomly divided into three groups—the microbubble-enhanced ultrasound (MEUS; further subdivided based on exposure intensity into MEUS1 [0.11 W/cm 2 ], MEUS2 [0.55 W/cm 2 ], and MEUS3 [1.1 W/cm 2 ]), ultrasound without microbubbles (US), and microbubbles without ultrasound (MB) groups. The pre- and post-treatment bleeding weight and visual bleeding scores were evaluated. The serum liver enzyme concentrations as well as the blood perfusion level represented by mean peak contrast intensity (PI) ratio in the treatment area were analyzed. The hemostatic mechanism was evaluated by histological and transmission electron microscopic examination of liver tissue samples. The MEUS subgroups 1–3 (grade 0–1, grade 0–2, and grade 1–2, respectively) exhibited significantly lower post-treatment visual bleeding scores than the US and MB groups (both, grade 3–4; all, P  < 0.05). Subgroups MEUS1 (0.346 ± 0.345 g) and MEUS2 (2.232 ± 2.256 g) exhibited significantly lower post-treatment bleeding weight than the US and MB groups (5.698 ± 1.938 and 5.688 ± 2.317 g, respectively; all, P  < 0.05). Additionally, MEUS subgroups 1–3 exhibited significantly lower post-treatment blood perfusion levels (PI ratios, 0.64 ± 0.085, 0.73 ± 0.045, and 0.84 ± 0.034, respectively) than the US and MB groups (PI ratios, 1.00 ± 0.005 and 0.99 ± 0.005, respectively; all, P  < 0.05). In the MEUS group, hepatic cells became edematous and compressed the hepatic sinus and associated blood vessels. However, the serum liver enzyme levels were not significantly altered. Microbubble-enhanced non-focused ultrasound does not significantly affect blood perfusion and liver function and can be used to induce rapid hemostasis in case of liver trauma.